DEVELOPMENT OF INTERACTIVE MEDIA TO ENHANCE SKILLS IN PROMOTING HIGHER-ORDER THINKING SKILLS (HOTS) MATHEMATICS QUESTIONS FOR ELEMENTARY SCHOOL ISLAMIC TEACHER EDUCATION STUDENTS: Pengembangan Media Interaktif Untuk Meningkatkan Keterampilan Dalam Mengembangkan Soal Hots Matematika Pada Mahasiswa PGMI - Wibowo, Ari (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
This study investigates the effect of the use of interactive media on the ability of elementary school Islamic teacher education students in understanding and developing questions that need the ability to think at a high level. The method used in this research is the Research and Development method. This research consists of 3 stages, namely: (1) introduction stage, (2) draft arrangement stage, and (3) development and evaluation stage. Based on the discussion, it can be concluded that: (1) interactive media developed has been interesting for 155 students involved in the main field trial, (2) The effect of the use of interactive media to the ability of elementary school Islamic teacher education students in understanding and developing questions that need higher order thinking skill refers to: (a) the average score of the understanding about the background and the definition of HOTS and the average score of the understanding about increasing the level of LOTS questions to HOTS questions in the group not using interactive media is lower than the group using interactive media, (b) the average score of misconception about HOTS in the group not using interactive media is higher than the group using interactive media, and (c) the students can make five HOTS questions in algebra, number and its operation material. It can be seen from the score of the students is 4,3796 on 5 scale.